Use Of Information Technology, Accounting Information Systems, Internal Control on The Quality of Financial Reporting Village-Owned Enterprises Ogan Ilir - Fitri Yusnita; Indah Khairunnis; Peny Cahaya Azwari (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to assess the impact of information technology adoption on the quality of financial reporting. 2) Ascertain how accounting information systems affect the standard of financial reports. 3) Assess the impact of internal control on the accuracy and reliability of financial statements. 4) Assess the impact of utilizing information technology, accounting information systems, and internal control on the accuracy and reliability of financial reports. This study utilizes a quantitative research methodology. The population under investigation consists of all Village-Owned Enterprises in Ogan Ilir Regency, totaling 227 Village-Owned Enterprises. Purposive sampling, based on predetermined criteria, is the method used for sampling in this study. The requirements encompass Village-Owned Enterprises that now employ information technology, apply accounting information systems, and implement internal control. According to these criteria, 92 samples that fulfill the criteria are acquired. The data analysis technique employed in this research uses the Eviews 12 software. The application of information technology has a beneficial and substantial impact on the caliber of financial reporting. Accounting information systems exert a favorable and substantial impact on the caliber of financial reporting. The internal control variable positively and significantly impacts the quality of financial reports, and all independent factors positively and significantly impact the quality of financial reports.